COVID-19-Associated Large- and Medium-Sized-Vessel Pathology: A Case Series - Chen, Stacey; Malas, Jad; Latson, Larry A., Jr; Narula, Navneet; Rapkiewicz, Amy V.; Williams, David M.; Pass, Harvey I.; Galloway, Aubrey C.; Smith, Deane E. (AORTA, 2022)
Background Coronavirus disease-19 (COVID-19) remains a public health crisis. The epidemiology of COVID-19-associated large- and medium-sized-vessel pathology is not well characterized. The aim of this study is to identify patients with possible COVID-19-associated large- and medium-sized-vessel pathology based on computed tomography (CT) imaging to provide insight into this rare, but potentially devastating, cardiovascular manifestation.Methods This is a single-center retrospective review of patients with CT chest, abdomen, and/or pelvis concerning for large- and medium-vessel pathology and confirmed COVID-19 infection from March 1, 2020 to October 31, 2020.Results During the study period, 6,553 CT reports were reviewed and pertinent imaging was identified in 139 patients. Of these, 8 patients (median age: 59 years, range 51–82) were COVID-19 positive. All patients had preexisting cardiovascular risk factors and three (37.5%) had an autoimmune disease. Four patients were never hospitalized for COVID-19. Among these, two presented to the hospital at a median of 39 days (range: 27–50) after their initial COVID-19 test with chest and back pain where imaging revealed extensive aortic pathology. One patient required surgical management for aortic pathology. All other patients were treated with expectant management and outpatient follow-up.Conclusion The clinical and radiological presentations of COVID-19-associated large- and medium-vessel pathology are heterogeneous and can be a late finding after COVID-19 recovery. Close clinical follow-up and surveillance imaging for large- and medium-sized-vessel pathology may be warranted in COVID-19 patients.
Keywords: COVID-19; aortitis; large-vessel vasculitis; medium-vessel vasculitis